The Effect of Crossword Puzzle Learning Media on Student Learning Outcomes in IPAS Class IV SD Karuna Dipa Palu - Lamanasa, Farsya Gabriella; Zulnuraini, Zulnuraini; Pendit, Sinta Satria Dewi; Rizal, Rizal; Guci, Ammar Abdullah Joni (FKIP - Universitas Riau, 2025)
This study aims to determine the effect of the Crossword Puzzle learning media on students’ learning outcomes in the IPAS subject for fourth-grade students at SD Karuna Dipa Palu. This research employed a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 17 students. Data were collected through observation and a multiple-choice test consisting of 25 items. The test instrument was validated using Pearson correlation analysis and its reliability was measured using Cronbach’s Alpha, yielding a score of 0.920, which indicates a highly reliable instrument. The data were analyzed using descriptive statistical analysis, the Shapiro-Wilk normality test, the N-Gain test, and hypothesis testing using the Paired Sample T-test with the assistance of IBM SPSS Statistics version 27. The results showed an increase in the average score from 62.59 in the pretest to 83.06 in the posttest. The N-Gain score of 0.6055 falls into the moderate category, indicating that the Crossword Puzzle media is fairly effective. The result of the Paired Sample T-test showed a significance value of 0.000 < 0.05, which led to the rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (Hₐ), indicating that the use of Crossword Puzzle in classroom learning has a significant effect on students’ learning outcomes. It can therefore be concluded that the use of this medium is effective in improving learning outcomes in IPAS and can be recommended as an interactive and enjoyable alternative learning media for elementary school students.